2009
DOI: 10.2174/1874120700903010001
|View full text |Cite
|
Sign up to set email alerts
|

A Fall and Near-Fall Assessment and Evaluation System

Abstract: The FANFARE (Falls And Near Falls Assessment Research and Evaluation) project has developed a system to fulfill the need for a wearable device to collect data for fall and near-falls analysis. The system consists of a computer and a wireless sensor network to measure, display, and store fall related parameters such as postural activities and heart rate variability. Ease of use and low power are considered in the design. The system was built and tested successfully. Different machine learning algorithms were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…53 Falls are commonly measured by self-report. With new technological developments in monitors and sensors, falls may be assessed by direct measurement in the future, 54 although the intermittent nature of falls could make measurement challenging. Self-report can be measured by simple recall such as "In the past month, have you had any fall including a slip or trip in which you lost your balance and landed on the floor or ground or lower level" 50 or can be measured by detailed daily fall diaries or calendars.…”
Section: Falls Assessmentmentioning
confidence: 99%
“…53 Falls are commonly measured by self-report. With new technological developments in monitors and sensors, falls may be assessed by direct measurement in the future, 54 although the intermittent nature of falls could make measurement challenging. Self-report can be measured by simple recall such as "In the past month, have you had any fall including a slip or trip in which you lost your balance and landed on the floor or ground or lower level" 50 or can be measured by detailed daily fall diaries or calendars.…”
Section: Falls Assessmentmentioning
confidence: 99%
“…Fall-detection algorithms detect different phases of a fall event: (1) motion prior to impact based on high velocity [46,47] and fast postural changes or free falls [48,49]; and (2) the impact itself based on high acceleration [50,51], a rapid change in acceleration and end posture [52,53], or reduced general activity after the impact [51]. In earlier studies, Kangas et al found that a waist-worn triaxial accelerometer with a simple algorithm was sufficient for fall detection [54,55].…”
Section: Fall Detectionmentioning
confidence: 99%
“…However, near-falls (or recoverable imbalances) are common events for many older adults and are clinically relevant markers of falls worthy of further study [25]- [26]. For example, investigators have found that older adults who report multiple near falls (such as missteps or stumbles) are more likely to go on to fall [27].…”
Section: Introductionmentioning
confidence: 99%